"Back to the Future" Therapy: Its Present Relevance, Promise, and Implications - Farnsworth, Jacob; Sewell, Kenneth W. (Pragmatic Case Studies in Psychotherapy, 2010)
Palgi and Ben-Ezra (2010) describe an intriguing approach to the treatment of acute stress responses in persons whose memory for a recent traumatic event has not yet consolidated -- an approach they call "Back to the Future" therapy (BFT). The present article examines BFT on several dimensions: theoretical fidelity, applicability, and potential for empirical investigation. BFT shows considerable promise as a treatment for a subset of persons who experience a traumatic stressor. The greatest challenges now for users of BFT include both identifying persons most likely to benefit from BFT, and systematically evaluating the effectiveness of the approach.